2020
DOI: 10.1109/access.2020.2984170
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Spatially Offset Raman Spectroscopy to Profile Molecular Composition in Bone

Abstract: Spatially offset Raman spectroscopy (SORS) offers the prospect of collecting spectral information detailing the molecular composition of biomaterials at greater depths below the surface layers than are normally probed by conventional Raman spectroscopy. By collecting off-axial scattered light, the technique overcomes the large background from in-line light within scattering media. In this paper we present a configuration which enables the highly efficient collection of spectral markers, indicative of bone heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We based the construction of our SHORS system around a DMD‐based SORS arrangement, as shown in Figure a, where offset value can be controlled by the radius Δ x of the pattern (more detail concerning the theory and analysis of DMD‐based SORS systems are described in previous studies [ 15,28 ] ). By placing a simple webcam at the sample position, we show the optical alignment of the system relative to the position of a laser spot (pink) and the image (purple) created by illuminating the DMD with white light (via the optical fiber that would normally be connected to the SHS), for the different DMD patterns associated with offset values, 0, 0.4, 0.8, and 1.0 mm, Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We based the construction of our SHORS system around a DMD‐based SORS arrangement, as shown in Figure a, where offset value can be controlled by the radius Δ x of the pattern (more detail concerning the theory and analysis of DMD‐based SORS systems are described in previous studies [ 15,28 ] ). By placing a simple webcam at the sample position, we show the optical alignment of the system relative to the position of a laser spot (pink) and the image (purple) created by illuminating the DMD with white light (via the optical fiber that would normally be connected to the SHS), for the different DMD patterns associated with offset values, 0, 0.4, 0.8, and 1.0 mm, Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, a number of different variants of the SORS technique have emerged, [ 12–15 ] including fiber‐based SORS, digital micromirror device (DMD)‐based SORS (with discrete and continuous offset patterns), wavelength modulated SORS, and SORS using custom machined optical lenses. However, with many of these innovations, the need for sophisticated data processing has remained, particularly in systems such as those based upon DMDs (where, although the physical movement of large optical elements to make measurements at different offsets has been eliminated, the challenge has instead been translated to an increased complexity in signal processing).…”
Section: Introductionmentioning
confidence: 99%
“…Other Raman methods, such as Spatially Offset Raman Spectroscopy (SORS) and Transmission Raman Spectroscopy (TRS) were reported to give better signals for sub-surface spectra collection (Vardaki et al, 2015;Ghita et al, 2016;Matousek and Stone, 2016). Despite their applications for imaging other tissue such as bone (Matousek et al, 2006;Cui et al, 2020), to the best of our knowledge, these techniques have not been reported for cartilage imaging.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Recently, measuring in or through biological tissue has been made possible via surface-enhanced spatially offset Raman spectroscopy (SESORS). [23][24][25][26] In spatially offset Raman spectroscopy, Raman-scattered light is collected from regions offset from the point of laser excitation at the sample, which allows a preferential collection of the subsurface spectra. [27] Using the SESORS method, Stone et al reported successful detection of Raman signals after injection of encapsulated SERS NPs into a porcine tissue block with a thickness of 20 mm.…”
Section: Introductionmentioning
confidence: 99%